Parade Trucks in Contemporary Cultural Trends: Identity, Influence, and the Expansion of Modern Musical Spaces in Thailand - Poshakrishna, Pakaus (MCU Haripunchai Review, 2026)
This paper examines Parade Trucks as a contemporary cultural phenomenon that plays a significant role in creating and redefining Thai identity. Parade Trucks are spaces that reflect the dynamics of Thai society in a globalized world through the fusion of traditional and modern music, connecting local culture with new forms of entertainment that align with people’s tastes and localization. At the same time, Parade Trucks serve as temporary public spaces that allow people to participate in singing, dancing, socializing, and building social networks. This aligns with Ray Oldenburg’s concept of "Third Place," which emphasizes the need for social spaces beyond home and work to foster a sense of community and relieve the stress of fast-paced urban living under a capitalist system. Furthermore, Parade Trucks have an important economic dimension, as Parade Trucks are often part of traditional events such as candle processions, the Phi Ta Khon festival, and other holy ceremonies. These events stimulate local commerce, from restaurants and beverages to local products, generating income and enhancing community vitality, along with cultural and social dimensions. Therefore, Parade Trucks serve not only as a tool for cultural preservation. The parade culture continues to negotiate the meaning of Thainess in a new dimension that is more open, flexible, and diverse, reflecting a Thainess that is not static but changes and adapts to the context of contemporary society through the new generation’s definition of values that are not tied to state power.